Integrated Computational and Experimental Discovery of a Promising Xanthine Derivative with Anticancer Potential Targeting EGFR - Elkaeed, Eslam B.; Yousef, Reda G.; Elkady, Hazem; Al-ghulikah, Hanan A.; Ibrahim, Ibrahim M.; Soliman, Omar A.; Husein, Dalal Z.; Doghish, Ahmed S.; Metwaly, Ahmed M.; Eissa, Ibrahim H. (Current Cancer Drug Targets, 2025)
<span class=
Keywords: Xanthine